UZBEK FOLK COSTUME IN MODERN FASHION DESIGN - Umida Abdukhashimovna Vakhidova (European Science Publishing, 2023)
The article considers the Uzbek folk costume as a source of inspiration in the design design of modern clothing. The stages of the spread of elements of the Uzbek national costume in the world fashion are investigated.
Keywords: folk costume, uzbek national clothes, ikat, tunic cut, fashion.